Decision-Making Method Based on a Comprehensive Assessment of the Effectiveness of the Radio Frequency Spectrum - P. Yu. Lakizo (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
One of the main problems in the use of the radio frequency spectrum is its scarcity. This is due not only to its natural properties as a resource, but also to the inefficiency of its use. Work in this direction was carried out by scientists. In order to release the inefficiently used part of the radio frequency spectrum, it is necessary to develop management measures and mechanisms that create the most unfavorable conditions for the operation of this part of the spectrum by operators. The article discusses proposals for the implementation of the methodology, the model and criteria for a symbolic description of the assessment of the effectiveness of the use of the radio frequency spectrum, including information and software implementation of a multi-agent system that allows for automated decision making, for a comprehensive assessment of the effectiveness of the use of the radio frequency spectrum. A model of the overall efficiency of using the radio frequency spectrum based on three types of efficiency has been proposed, and a scale of intervals for these types has been developed. An assessment of the efficiency of the radio frequency spectrum based on a reference network of cellular mobile communications has been performed. A decision making variant based on the results of evaluating this efficiency is presented.